A Wild Allele of Pyrroline-5-Carboxylate Synthase1 Leads to Proline Accumulation in Spikes and Leaves of Barley Contributing to Improved Performance Under Reduced Water Availability - Frimpong, Felix; Windt, Carel W.; van Dusschoten, Dagmar; Naz, Ali A.; Frei, Michael; Fiorani, Fabio (Frontiers in Plant Science, 2021)
Water stress during spike development strongly affects final grain yield in cereals. Proline, an osmoprotectant amino-acid, may contribute to alleviating the effects of cell and tissue dehydration. We studied five spring barley genotypes contrasting in their drought response, including two introgression lines, S42IL-143 and S42IL-141, harboring a Pyrroline-5-carboxylate synthase1- P5cs1 allele originating from the wild barley accession ISR42-8. We tested the hypothesis that barley genotypes harboring a wild allele at P5cs1 locus are comparatively more drought-tolerant at the reproductive stage by inducing proline accumulation in their immature spikes. At the booting stage, we subjected plants to well-watered and water stress treatments until physiological maturity. Several morpho-physiological traits had significant genotype by treatment interaction and reduction under water stress. Varying levels of genotypic proline accumulation and differences in water stress tolerance were observed. Spike proline accumulation was higher than leaf proline accumulation for all genotypes under water stress. Also, introgression lines carrying a wild allele at P5cs1 locus had a markedly higher spike and leaf proline content compared with the other genotypes. These introgression lines showed milder drought symptoms compared with elite genotypes, remained photosynthetically active under water stress, and maintained their intrinsic water use efficiency. These combined responses contributed to the achievement of higher final seed productivity. Magnetic resonance imaging of whole spikes at the soft dough stage showed an increase in seed abortion among the elite genotypes compared with the introgression lines 15 days after water stress treatment. Our results suggest that proline accumulation at the reproductive stage contributes to the maintenance of grain formation under water shortage.